Reluctant, Ambivalent and Progressive: Educators’ attitudes towards the use of generative artificial intelligence in Enabling Education - James, Trixie; Pike, John; Andrews, Grant; Valentine, James; Brickhill, Michael; Sharp, Julie; Ulpen, Tamra (Journal of University Teaching and Learning Practice, 2025)
The integration of generative artificial intelligence (GenAI) into higher education has recently become a significant topic of discussion, especially in Enabling Education. Enabling Education programs are designed to prepare students for undergraduate studies by developing foundational literacy skills. However, many educators grapple with whether GenAI is an appropriate tool for supporting students' learning needs or whether it undermines the development of core academic literacies. This study comprises a survey with academics from Enabling programs at 14 universities across Australia. The survey explores educators’ perspectives toward GenAI tools, including their own use of AI-generated content in teaching and their views on students utilising these tools. Our findings show that educators’ perspectives can be categorised as Traditionalist (GenAI’s disruption viewed as a threat to learning), Progressive (GenAI’s opportunities viewed as beneficial to learning), and Ambivalent (GenAI viewed with uncertainty or a mixture of Progressive and Traditionalist ideas). However, these perspectives are expressed in complex and nuanced ways, with educators often holding a range of views that reveal the complicated impact of GenAI. Understanding these perspectives is crucial for addressing potential barriers and facilitating the effective implementation of GenAI in Enabling education.